2019
DOI: 10.4067/s0034-98872019000700877
|View full text |Cite
|
Sign up to set email alerts
|

Factores asociados a caídas en adultos mayores chilenos: evidencia de la Encuesta Nacional de Salud 2009-2010

Abstract: En representación de todos los integrantes del grupo ELHOC) Factors associated with falls in older adults in chile. Analysis of the National Health Survey 2009-2010 Background: A decrease in functional capacity due to ageing is one of the main risk factors for falls in older people. Aim: To investigate factors associated with falls in Chilean older adults. Material and Methods: We analyzed the self-reports of falls of 1,334 people aged ≥ 60 years who answered the National Health Survey 2009-2010. Falls during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
1
0
0
3
Order By: Relevance
“…This coincides with a suggestion in the recently published global guidelines for falls prevention [1].Limited national studies have reported interventions of this type in older adults living in their homes [28]. National publications on falls in older people are generally only descriptive in nature [40,41]. Against this background, in the current study, we expect to demonstrate the effects of the model among older adults according to the following variables: fall frequency, fall perception, and risk factor management.…”
Section: Discussionsupporting
confidence: 85%
“…This coincides with a suggestion in the recently published global guidelines for falls prevention [1].Limited national studies have reported interventions of this type in older adults living in their homes [28]. National publications on falls in older people are generally only descriptive in nature [40,41]. Against this background, in the current study, we expect to demonstrate the effects of the model among older adults according to the following variables: fall frequency, fall perception, and risk factor management.…”
Section: Discussionsupporting
confidence: 85%
“…Em pessoas idosas brasileiras da comunidade, 27,0% sofreram uma queda em 12 meses (ELIAS FILHO et al, 2019), semelhante às do espaço rural, com uma prevalência de quedas de 27,9% (SANTOS et al, 2019). Estudos internacionais trazem a prevalência de quedas de 37,2% no Chile (LEIVA et al, 2019), 29,6% nos Estados Unidos (LEE, 2021) e 32,2% na Malásia (ABU BAKAR et al, 2021).…”
Section: Discussionunclassified
“…Em um estudo realizado no sul do Brasil, 56,4% das pessoas idosas avaliadas sofreram uma queda na própria casa (VIEIRA et al, 2018). O ambiente doméstico em condições impróprias para pessoas idosas -presença de tapetes soltos, escadas sem corrimão para apoio, iluminação inadequada, mobília mal distribuída obstruindo caminhos, presença de animais domésticos, superfície escorregadia, calçados inapropriados e declive acentuado -torna-se um importante fator de risco para a ocorrência de quedas (GIACOMINI;FHON;RODRIGUES, 2020;KIM et al, 2020;LEIVA et al, 2019;NOGUEIRA et al, 2021;TAVARES;ARAÚJO;NUNES, 2021).…”
Section: Introductionunclassified
“…Del mismo modo Chile en el 2019, presentó una prevalencia de un 37.2% en caídas, donde el 39. % tuvo problemas auditivos, el 59.1% tuvo mala calidad de visión un 48.9% con deterioro cognitivo y el 44.1% estado de bienestar (9).…”
Section: Planteamiento Del Problemaunclassified